Defining the process of a cardiovascular risk assessment program: Lessons learned from cardiac assessment of elite soccer players in the United Kingdom - Speers, C.; Seth, A. N.; Patel, K. C.; Rakhit, D. J.; Gillett, M. J. (Clinical Journal of Sport Medicine, 2019)
Retrospectively analyze the cardiac assessment process for elite soccer players, and provide team physicians with a systematic guide to managing longitudinal cardiac risk. Design: Descriptive Epidemiology Study. Setting: Cardiac assessments incorporating clinical examination, 12-lead ECG, echocardiography, and health questionnaire. Participants: Soccer players at 5 professional clubs in England, the United Kingdom. Intervention: Data was retrospectively collected, inspected, and analyzed to determine their clinical management and subsequent follow-up. Results: Over 2 years, 265 soccer players, aged 13 to 37 years with 66% of white European ethnicity, were included in the cohort. Eleven percent had "not-normal" assessments, of these assessments, 83% were considered gray screens, falling into three broad categories: structural cardiac features (including valvular abnormalities), functional cardiac features, and electrocardiogram changes. After cardiology consultation, all assessments were grouped into low, enhanced and high-risk categories for ongoing longitudinal risk management. Overall clear-cut pathology was identified in 2%. Conclusions: Cardiovascular assessment is a vital tool in identifying athletes at risk of sudden cardiac death to mitigate their risk through surveillance, intervention, or participation restriction. The decision whether a player is fit to play or not requires a robust risk assessment followed by input from a multidisciplinary team that includes both the team physician and cardiologist. This educational article proposes a clinical management pathway to aid clinicians with this process. Clinical Relevance: Sudden cardiac death is the important medical cause of death during exercise. The team physician should assume responsibility for the management of the longitudinal risk of their players' cardiac assessments in conjunction with sports cardiologist.